Behaviour of Community Pharmacy Service Provider towards Self Medication Services: Study in Two Cities in West Java - Roseno, Mohammad; Widyastiwi, Widyastiwi; Alifia, Sarah; Rahmadhani, Melly Shafira (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Self-medication behavior is currently increasing in Indonesia. Community pharmacy service provider have an important role as the main source of information and recommendations for the community in self-medication. To be able to provide good self-medication services, good knowledge, attitudes, and practices are needed from pharmacists. This study was aimed to measure the knowledge, attitudes, and practices of pharmacists in providing self-medication services. The study was conducted with a cross-sectional design in pharmacies in Bandung City and Cianjur Regency in the period March-April 2021. A valid and reliable questionnaire was administered to 141 respondents who worked in pharmacies that were selected randomly, to measure the knowledge, attitudes, and practices related to self-medication. The inclusion criteria were community pharmacy service provider who worked permanently and were willing to fill out questionnaires. Exclusion criteria were intern worker and incomplete questionnaires. Results showed that community pharmacy service provider in Bandung City and Cianjur Regency had an average knowledge of 65.04% (moderate), attitudes 78.40% (good), and practice 85.59% (very positive) towards self-medication services. In self-medication behavior, knowledge of community pharmacy service provider was influenced by type of position (p0.05), self-medication attitude was influenced by type of pharmacies (p0.05), and self-medication service practice was influenced by location (p0.05). This study concludes that community pharmacy service provider in Bandung City and Cianjur Regency have a moderate knowledge, and good attitudes and very positive practices in self-medication services.